Macrophages During the Fibrotic Process: M2 as Friend and Foe - Braga, Tarcio Teodoro; Agudelo, Juan Sebastian Henao; Camara, Niels Olsen Saraiva (Frontiers in Immunology, 2015)
Macrophages play essential activities in homeostasis maintenance during different organism’s conditions. They may be polarized according to various stimuli, which subsequently subdivide them into distinct populations. Macrophages with inflammatory activity function mainly during pathological context, while those with regulatory activity control inflammation and also remodel the repairing process. Here, we propose to review and to present a concise discuss on the role of different components during tissue repair, including those related to innate immune receptors and metabolic modifications. The scar formation is directly related to the degree of inflammation, but also with the appearance of M2 macrophages. In spite of greater numbers of macrophages in the fibrotic phase, regulatory macrophages present some characteristics related to promotion of fibrosis but also with the control of scar formation. These regulatory macrophages present an oxidative metabolism, and differ from the initial inflammatory macrophages, which in turn, present a glycolytic characteristic, which allow regulatory ones to optimize the oxygen consumption and minimizing their ROS production. We will emphasize the difference in macrophage subpopulations and the origin and plasticity of these cells during fibrotic processes.